P-Convex Functions and Some of Their Properties. (21st May 2021) - Sezer, Sevda; Eken, Zeynep; Tınaztepe, Gültekin; Adilov, Gabil
Abstract: In this paper, the concept of p -convex function based on the definition of p -convex sets is given. Then fundamental characterizations and some operational properties of p -convex functions are presented. Furthermore, the relations between p -convex functions for different p values are obtained.